THE INTEGRATION OF THE MARKETING COMMUNICATIONS AND THEIR ROLE IN THE SUCCESSFUL DEVELOPMENT OF AN UNIVERSITY - Trifonova, L.I. (Kostanay State Pedagogical Institute, 2017)
Nowadays, there is only a small amount of companies that do not use marketing communications in their activity. Without them, the company becomes as if “deaf and dumb”. The impossibility of communication, of the maintenance of an effective dialogue with the target- audience, of the receiving of a qualitative feedback, makes the company product unknown, and so unnecessary. For the product to be known there is a need to tell about it, to tell to the potential interested people, in other words, with the target audience, in an accessible and clear language. The expansion of the educational technologies and of the new approaches in the area of education makes it necessary to be advertised and to make their recognition higher. Due to this, the importance of the communicational policy of the educational institutions is an essential element in their development process.
Keywords: marketing communications; education; higher education; university communications; integrated marketing communications; the program of marketing communications